CURRENT PRACTICE IN TEACHING ELEMENTARY ACCOUNTING. - Jones, Ralph Coughenour (The Accounting Review, 1937)
Abstract Last November a questionnaire on first-year accounting was mailed to all colleges and universities represented among the membership of the American Accounting Association. Replies received from fifty-three schools in the U.S. and Canada were used as the basis for a round-table discussion of various teaching methods and problems at the annual convention in Chicago last December. It is the purpose of the article to summarize these replies for the benefit of those who could not attend the round-table itself. No attempt will be made to measure or compare standards of instruction or to label one practice as good and another as bad. While a variation in standards is apparent, the differences in methods and objectives are even more marked. It would be futile, for instance, to compare a required freshman course in bookkeeping in a large city college of commerce with an accounting course for juniors or seniors in a liberal arts college, or with a course in a graduate school of business administration.